The Dilemma of Gender and Marital Validity in Khuntha Cases: A Comparative Legal Study of the Four Sunni Schools - Harahap, Khoirul Amru; Harahap, Najhan Parluhutan; Umar, Mohamad Toha (Jurnal Syariah dan Hukum Komparatif, 2025)
In Islamic jurisprudence, the validity of marriage is contingent upon clear gender classification, a condition that poses legal complexities in the case of khuntha (intersex individuals). Classical jurists recognized khuntha as a distinct legal category and developed nuanced rulings, particularly distinguishing between khuntha wādih and khuntha mushkil. However, advances in medical science and shifting socio-legal contexts necessitate a re-examination of these doctrines. This study adopts a doctrinal and comparative approach, analyzing the positions of the four Sunni schools—Hanafī, Mālikī, Shāfiʿī, and Hanbalī—on the permissibility of khuntha marriage. It engages classical legal texts, modern fatwas, and contemporary bioethical considerations to assess continuity and reform. The four schools unanimously prohibit marriage for khuntha mushkil without gender clarity, while permitting it for khuntha wādih upon identifiable signs. Divergences arise in their evidentiary standards and interpretive flexibility. Contemporary scholars increasingly advocate for the inclusion of medical criteria and expert consultation in gender determination. Islamic legal tradition provides a principled yet adaptable framework for addressing khuntha marriage. By integrating classical methodologies with contemporary scientific understanding, jurists can uphold Sharīʿah objectives while affirming the dignity and marital rights of intersex individuals. This reflects both fidelity to tradition and responsiveness to present realities.